2010
DOI: 10.1186/1471-2180-10-241
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Paracoccidioides brasiliensis phospholipase B involvement in alveolar macrophage interaction

Abstract: BackgroundPhospholipase B (PLB) has been reported to be one of the virulence factors for human pathogenic fungi and has also been described as necessary for the early events in infection. Based on these data, we investigated the role of PLB in virulence and modulation of the alveolar pulmonary immune response during infection using an in-vitro model of host-pathogen interaction, i.e. Paracoccidioides brasiliensis yeast cells infecting alveolar macrophage (MH-S) cells.ResultsThe effect of PLB was analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 33 publications
2
22
0
4
Order By: Relevance
“…Although V-ATPase inhibitors that have therapeutic applications have yet to be identified, the Prestwick Chemical Library is a useful resource for drug repurposing, as most of the compounds have known safety and toxicity profiles. In fact, cytotoxicity by alexidine dihydrochloride has been shown previously in Cryptococcus neoformans, C. albicans, and Paracoccidioides brasiliensis (55,56). Together, those studies and our current findings make alexidine dihydrochloride and thonzonium bromide attractive candidates to evaluate for repurposing as potential antifungal therapeutic drugs.…”
Section: Discussionsupporting
confidence: 84%
“…Although V-ATPase inhibitors that have therapeutic applications have yet to be identified, the Prestwick Chemical Library is a useful resource for drug repurposing, as most of the compounds have known safety and toxicity profiles. In fact, cytotoxicity by alexidine dihydrochloride has been shown previously in Cryptococcus neoformans, C. albicans, and Paracoccidioides brasiliensis (55,56). Together, those studies and our current findings make alexidine dihydrochloride and thonzonium bromide attractive candidates to evaluate for repurposing as potential antifungal therapeutic drugs.…”
Section: Discussionsupporting
confidence: 84%
“…The pathogenicity of SAPs, however, remains contentious (Correia et al 2010) with poor correlation found between individual SAP gene expression and epithelial damage (Naglik et al 2008). SAP expression is also dependent on environmental pH (Staib et al 2000), therefore, it is unsurprising that SAP production in C. albicans was not detected phenotypically in this study. The marked reductions in hyphal formation, which were induced by OligoG, were mirrored by alterations in the gene expression of PLB2, SAP4 and SAP6, evident by qPCR analysis.…”
Section: Discussionmentioning
confidence: 72%
“…) and local immune responses (Soares et al . ). While PL expression has, however, previously been shown not to correlate with RHE invasion in this model (Malic et al .…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the cryptococcal PLB is involved in cell wall stabilization (Siafakas et al, 2007). Like the related bacterial enzymes (Flieger et al, 2004;Pankhaniya et al, 2004), extracellular PLBs produced by pathogenic fungi are key players in adhesion to host cells (Ganendren et al, 2006;Soares et al, 2010), in cellular infection through membrane perturbation (Santangelo et al, 2004) and in the modulation of the lipid-mediated immune response (Noverr et al, 2003). Presumably, a PLB also contributes to symbiontic interactions such as nutrient exchange in mycorrhiza (Krause and Kothe, 2006).…”
Section: Introductionmentioning
confidence: 98%